REVIEW OF TREATMENT OUTCOME FOR THREATENED MISCARRIAGE IN THE FIRST TRIMESTER IN WOMEN WITH HISTORY OF STILL BIRTH AND/OR RECURRENCE MISCARRIAGE AT NGHE AN OBSTETRICS AND PAEDIATRICS HOSPITAL FROM JANUARY 2022 TO JULY 2022 (Vietnam Journal of Community Medicine, 2022)
Objectives: Recurrent miscarriage is defined as 2 or more consecutive miscarriages before the22th week of gestation. Early detection of causes of miscarriage can lead better treatmentoutcomes.Materials and methods: Cross-sectional descriptive study on 52 patients with a history ofmiscarriage and/or consecutive miscarriage at Nghe An Obstetrics and Pediatrics Hospital fromJanuary 2022 to June 2022.Results: Our research has shown that: 30% of pregnant women experienced recurrentpregnancy loss and 88,8% of pregnant women experienced consecutive stillbirth. The prevalenceof recurrent pregnancy loss and consecutive stillbirths due to unknown causes accounted for thehighest rate of 84.7%. The incidence of successful treatment and treatment failure of threatenedmiscarriage was relatively 75 % and 25%. The average length of stay for a hospitalization was 18± 10,8 days.Conclusions: History of consecutive miscarriage 30%; consecutive stillbirths 88.8%; unknowncause 84.7%. Hospitalization for abdominal pain 40.4%. Treatment success 75%, failure 25%. Thehospital stay 18 ± 10.8 days.
Keywords: Threatened miscarriage, recurrent miscarriage, recurrent pregnancy loss, consecutive stillbirth.